1979
DOI: 10.1002/hlca.19790620620
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Optical Activity of all‐trans, mono‐cis, and di‐cis Carotenoids: Temperature Dependent Circular Dichroism

Abstract: SummaryThe CD. spectra of carotenoids with an asymmetric centre at C(3) have the following unusual features: 1) All-trans and di-cis compounds with two end-rings, at least one of which possesses an asymmetric C-atom, have very similar CD. spectra, whereas the corresponding mono-cis compounds give mirror-image CD. spectra; 2) In carotenoids or apocarotenoids with only one end-ring all-trans and mono-cis compounds have the same CD. spectra; 3) The CD. spectra of such carotenoids are strongly temperature dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
17

Year Published

1981
1981
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 16 publications
0
39
0
17
Order By: Relevance
“…[18] A chiral perturbation of the polyene chain is not expected to occur in (R)-5 and, in addition, Cotton effects in the absorption region of the polyene chain above 400 nm are difficult to detect. [19,20] In some colorless glycerides, weak Cotton effects were observed around 220 nm (n-p* transitions of the ester group), [21][22][23][24] sometimes with opposite signs for the same enantiomer. [25] The measurement of the weak specific rotation of lysophospholipids requires high compound concentrations (3-5 %).…”
Section: Resultsmentioning
confidence: 97%
“…[18] A chiral perturbation of the polyene chain is not expected to occur in (R)-5 and, in addition, Cotton effects in the absorption region of the polyene chain above 400 nm are difficult to detect. [19,20] In some colorless glycerides, weak Cotton effects were observed around 220 nm (n-p* transitions of the ester group), [21][22][23][24] sometimes with opposite signs for the same enantiomer. [25] The measurement of the weak specific rotation of lysophospholipids requires high compound concentrations (3-5 %).…”
Section: Resultsmentioning
confidence: 97%
“…Optical antipodes are required in order to establish the reliability of CD in this region. 13 In our experiments (all-E, 3R, 3ЈR)-zeaxanthin (1) had a positive CD (⌬ ∼9.2) in the 450-530 nm region, as had the optically inactive (3R, 3ЈS)-mesozeaxanthin (3) (⌬ 8-10) and ␤,␤-carotene (⌬ ∼10). The wavelength region above 400 nm is consequently disregarded in the present work.…”
Section: Is (9z)-"meso"-zeaxanthin Optically Active?mentioning
confidence: 95%
“…13,19,20 In ␤,␤-carotene each of the half-chair cyclohexene rings occur in rapidly interconverting conformers. Introduction of hydroxy substituents at C-3 or C-2 in the ␤-ring changes the conformational equilibrium which determines the Cotton effect.…”
Section: Rationalisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituents at the b-end group change the conformational equilibrium even more, and the energetically favored conformer becomes increasingly populated. It has been found that RO substituents at C(3) of the b-end group adopt the equatorial position [10] [11]. In (3R,3'R )-zeaxanthin (7), each of the b-end groups occurs in two conformations: B up and B down ( Fig.…”
mentioning
confidence: 98%